1993
DOI: 10.1037/0278-6133.12.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with severity of depression and high-risk sexual behavior among persons diagnosed with human immunodeficiency virus (HIV) infection.

Abstract: Whereas some people appear to cope after learning that they have human immunodeficiency virus (HIV) infection, others experience depression and suicidal ideation. In this study, 142 persons with HIV infection were administered the Center for Epidemiological Studies Depression Scale (CES-D). High levels of depression were predicted by lower perceived social support, attributions that health was influenced more by chance, high-risk sexual behavior practices, and greater number of HIV illness symptoms and greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
144
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(157 citation statements)
references
References 11 publications
11
144
1
1
Order By: Relevance
“…Similarly, patients with head and neck cancer who participated in a support group experienced higher levels of emotional wellbeing and mental health [39], while depressed HIV-infected males who attended a social support group showed reductions in depression, hostility and anxiety [40]. However, as with MS support groups, not all research has revealed such positive results.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, patients with head and neck cancer who participated in a support group experienced higher levels of emotional wellbeing and mental health [39], while depressed HIV-infected males who attended a social support group showed reductions in depression, hostility and anxiety [40]. However, as with MS support groups, not all research has revealed such positive results.…”
Section: Discussionmentioning
confidence: 82%
“…HIV incidence is four-fold higher among psychiatric out-patients than the general population (Beyeret al 2007). Researchers have suggested that in order to reduce STI/HIV among vulnerable populations, including women engaging in transactional sex, we must improve their mental health (Kelly et al 1993;Nyamathi and Flaskerud 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Second, there is evidence that debilitating psychosocial problems have a negative impact on maintaining adherence to complex treatment regimens, which is a threat to the individual's health as well as a serious public health problem (Catz, Kelly, Bogart, Benotsch, & McAuliffe, 2000;Chesney, 2003;Ickovics et al, 2002;Pratt et al, 2001;Tucker, Burnam, Sherbourne, Kung, & Gifford, 2003). Third, maladaptive coping is associated with high-risk sexual behavior that escalates the spread of HIV disease (Kelly et al, 1993) Fourth, there is mounting evidence that high levels of stress may influence disease progression by way of immunological impairment (Robinson, Matthews, & Witek-Janusek, 2000). …”
mentioning
confidence: 99%